Analysis Of Factors Affecting Village Financial Accountability - Lukman Hakim; Tengku Juhri Agustan; Sahnan Rangkuti (Jurnal ASET (Akuntansi Riset), 2022)
This research aims to test whether the implementation of good governance, financial management, quality of human resources, and community participation influence village financial accountability in the Batang Kuis sub-district and Percut sei Tuan sub-district. This research is a quantitative study with causal associative analysis. It uses primary data through questionnaires directly given to respondents, namely village heads, village secretaries, village treasurers, and village communities in villages located in Batang Kuis and Percut sei Tuan sub-districts. The sampling technique is purposive sampling. The test tool used in this study is WarpPLs 3.0. The results showed the implementation of good governance, financial management, the quality of human resources and community participation had a positive and significant effects on village financial accountability in Batang Kuis and Percut sei Tuan sub-district,  with a p-value of 0.05, and goodness of fit can be said to be a research model with a fit model.